Croton cajucara Essential Oil Nanoemulsion and Its Antifungal Activities - Mariana M. B. Azevedo (MDPI AG, 2021)
The purpose of this study was to develop a stable nanoemulsion (NE) containing Croton cajucara 7-hydroxycalamenene-rich essential oil (NECC) with antifungal activity. The NECCs were prepared using an ultrasonic processor with Pluronic® F-127 as the aqueous phase. In order to evaluate the NECCs, the droplet size, polydispersity index (PdI), percentage of emulsification, and pH were determined along with a stability study. The NECC selected for the study had 15% surfactant, showed 100% emulsification, Pdl of 0.249, neutral pH, droplet diameters of about 40 nm, and remained stable over 150 days at room temperature. In addition, the NECC activity against some species of Zygomycetes and Candida, as well as the potential to inhibit fungal extracellular proteases, were assessed, and, finally, the hemolytic activity was evaluated. The best NECC antifungal activities were against Mucorramosissimus (Minimal inhibitory concentration (MIC) = 12.2 μg/mL) and Candida albicans (MIC = 25.6 μg/mL). The highest extracellular protease activities of M. ramosissimus and C. albicans were detected at pH 3 and 4, respectively, which were totally inhibited after NECC treatment. The NECC showed no hemolytic effect at the highest concentration tested (2 mg/mL).